Effectiveness of the SAVI Learning Model Based on Flipped Learning for Enhancing Creative Thinking Skills in Early Childhood Education in Indonesia - Mangsi, Raya; Maryani, Leni; Lestari, Andi Yustira; Swara, Marrieta Moddies; Kurniawa, Andri (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to determine the effectiveness of the SAVI learning model based on flipped learning in improving creative thinking skills in children. This study is a quantitative research with a meta-analysis approach. Data for this study were obtained from 23 studies that met the inclusion criteria. The process of searching for data through Google Scholar, Mendeley, ERIC, ScienceDirect and Wiley databases must be indexed by Sinta or Scopus. Analyze the data with the help of Microsoft Excel and JASP. The analysis of 23 effect sizes concluded that the summary effect size value ( rRE = 0.931; z = 9.156; p < 0.001). These findings show that applying the SAVI learning model based on flipped learning significantly influences creative thinking skills in children in the very high effect size category. This research provides information on the world of education in Indonesia and education in the future.